ANALISIS HUBUNGAN PAPARAN DEBU SEMEN DENGAN KAPASITAS VITAL PARU PADA PEKERJA DEPARTEMEN PRODUKSI DI PT. X JAWA TENGAH - Pradesi, Regina; Suwondo, Ari; Jayanti, Siswi (Jurnal Kesehatan Masyarakat (e-Journal), 2018)
Cement dust is particle of cement produced from the cement production process. Cement dust has varied sizes, at PT. X biggest cement dust measuring 90 Âµ. Exposure to cement dust in the occupational environment may affect the pulmonary vital capacity. A decrease in pulmonary vital capacity may affect the vital performance due to fatigue. Individual characteristics that affect the pulmonary vital capacity are age, nutritional status, gender, history of lung disease, smoking habits, exercise habits, and work period. The design study that is conducted by quantitive with cross sectional approach. The instruments were used questionnaires, spirometers, personal air sampling pump and aluminium cyclone, scales, stature meter. The population in this study are 51 production department workers consist of plant patroller and operator uses total sampling. The results showed there were 10 respondents who get exposure dust â‰¥3mg/m3 (above NAB). Bivariate analysis showed the related variables were smoking habit (p = 0,035), exercise habit (p = 0,048), work period (p = 0,041). While unrelated variable were age (p = 0,575), nutritional status (p = 0,692), history of lung disease (p = 0,611), exposure of dust (p = 0,139). Work period is a risk factor towards pulmonary vital capacity and exercise habit is a protective factor against the decline in pulmonary vital capacity in production department workers of PT. X.